The mechanism of social interaction deficits in attention-deficit/hyperactivity disorder children: the role of cognitive flexibility - Liu, Zicheng; Yin, Weizhen; Chen, Ziyuan; He, Wuming; Zhang, Zhuoqun; Sun, Sai; Yu, Meng (Frontiers in Psychiatry, 2025)
BackgroundAttention-deficit/hyperactivity disorder (ADHD) is one of the most prevalent mental disorders among children in China. Although the relationship between ADHD symptoms and social interaction deficits has been empirically examined, cognitive flexibility (CF), as a core factor theoretically contributing to ADHD, has still been less studied.AimThis study aims to explore how CF influences social interaction deficits using both tradition method (questionnaire surveys) and novel paradigms (Reinforcement learning).MethodIn study 1, we recruited 20 clinically urban Chinese children diagnosed with ADHD (M = 9.50, SD = 1.82) and 23 control group children (M = 9.80, SD = 1.86). Questionnaires were used to assess ADHD symptoms, CF, and social interaction deficits (including social self-efficacy and emotion problems). Furthermore, a mediation analysis was conducted. In study 2, 21 urban Chinese children diagnosed with ADHD (M = 10.00, SD = 2.53) and 21 control children (M = 9.19, SD = 1.44) completed a two-stage Markov Decision Task to measure their CF.ResultsStudy1 showed that CF mediated the relationship between ADHD symptoms and social interaction deficits in children with ADHD. Study 2 demonstrated that the control group employed both model-based and model-free cognitive strategies; however, the ADHD group did not demonstrate either strategy. These findings indicate a significant difference in CF between ADHD and control groups, particularly in their selection of cognitive strategies.ConclusionTo sum up, the findings suggest that a low level or deficiency in CF may be a key factor contributing to social problems in children with ADHD. Future research directions are further discussed.